Effects of Lawn Tennis Association mini tennis as task constraints on children's match-play characteristics. Issue 22 (17th November 2017) - Fitzpatrick, Anna; Davids, Keith; Stone, Joseph Antony
ABSTRACT: The Lawn Tennis Association's mini tennis (MT) is a modified version of tennis consisting of progressive stages; however, there have been few attempts to evaluate how MT might shape performance behaviours. Here, we examine effects of playing MT on the emergence of children's match-play behaviours in 48 junior tennis players. Performance in 1010 match-play points were filmed and coded across 4 tennis stages (MT Red, MT Orange, MT Green and Full Ball), using a notational analysis system. Recorded performance variables included rally length, first serve percentage and shot type, for the purpose of analysing inter-stage comparisons. Results showed a series of specific adaptations to playing characteristics across the stages, including rally length, shot variety and serve success. MT Red rallies (7.36 ± 6.06) were longer than Full Ball rallies (3.83 ± 2.40), and a higher percentage of forehands were played at MT Red (66.40 ± 8.49%) than at Full Ball stage (45.96 ± 6.47%). Findings suggested that MT stages can afford children more opportunities to develop their skills and elicit different match-play characteristics than Full Ball task constraints. Coaches, therefore, should consider the nature of emergent adaptations when designing practice environments to facilitate learning in young tennis players.